The Effectivenes Of Blended-Learning In Listening Subjects At The 2nd Semester Students Of English Education Study Program At Universitas Nias - Zebua, Elwin Piarawan; Harefa, Afore Tahir; Harefa, Trisman (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Blended Learning might be one of many choices that educators and students apply in listening class. Post pandemic time, numbers of synchronous and asynchronous learning are arranged to cope with better learning. This research was conducted to see the effectiveness of Blended Learning when applied in Listening skill subjects. The subject of the research was 64 students of the 2nd semester of English Education Study Program at Universitas Nias in 2022/2023 who took Intermediate Listening class. The data gained from the observation and semi-structured interviews to both lecturer and students to gain clear data, and were analyzed through descriptive qualitative analysis. The result of the research revealed that the Blended Learning in Intermediate Listening class was considerably effective but considered as a new style of learning, need more improvement on competence, digital literacy and dedication.